Nonsynonymous HTR2C polymorphism predicts cortisol response to psychosocial stress II: Evidence from two samples. (August 2016) - Way, Baldwin M.; Brown, Kirk Warren; Quaglia, Jordan; McCain, Nancy; Taylor, Shelley E.
Highlights: We examined cortisol reactivity to a social evaluative stressor in the laboratory. Two serotonin polymorphisms were tested: Cys23Ser in the HTR2C gene and the 5-HTTLPR. The HTR2C Cys23 allele was associated with greater cortisol reactivity. The 5-HTTLPR short/short genotype was associated with greater cortisol reactivity. Results underscore the importance of the serotonin system in cortisol reactivity. Abstract: The 5-HT2C receptor is the primary serotonin receptor located in the corticotrophin releasing hormone (CRH) neurons of the hypothalamus. These neurons initiate the signaling cascade that culminates in cortisol release. Therefore, genetic variation in the 5-HT2C receptor gene ( HTR2C ) is a prime candidate for affecting cortisol reactivity to stress. Accordingly, we examined the association of a nonsynonymous polymorphism (Cys23Ser; rs6318) in HTR2C with stress reactivity in two Trier Social Stress Tests conducted at separate sites. In both Study 1 ( N = 128) and Study 2 ( N = 185), Cys23 homozygous females and hemizygous males had greater cortisol reactivity. There was no relation between this polymorphism and self-reported affective response (Studies 1 and 2) or cardiovascular reactivity (Study 2). Additionally, the short/short genotype of a polymorphism (5-HTTLPR) in the serotonin transporter gene was associated with greater cortisol reactivity in Study 1 as well as in Study 2 (previously reported). The Cys23Ser polymorphism and the 5-HTTLPR were independently associated with cortisol reactivity in both studies. These findings emphasize the important role of genetic variation in the serotonin system on regulating cortisol reactivity to social evaluative stress. Comparison of the present associations with those of prior studies underscores the likely importance of situational and psychological factors in determining the direction and magnitude of the association between genotype and phenotype.